Présence en public : expérimenter la performance comme « théâtre » (Itinera, 2017)
Our proposal questions the participation of the public in the performance. An aspect which we are going to develop is the object of the performance as effective strategy which assures the success in one paradigm participative. The stage in three D of the performance is a space of meeting between the actor/performer and the spectator/performer. The stage in three D transforms the performative work into collective happening. We are going to study in particular examples from our performative/participative practice (as The Two Gullivers), but also from Marina Abramovic's practice.